STRATEGI PENGEMBANGAN KOPERASI SYARIAH (Studi Kasus Koperasi Syariah Bina Usaha Bunda Kecamatan Gunung Tuleh Kabupaten Pasaman Barat) - Inda Yani; Rusyaida (CV. ADIBA AISHA AMIRA, 2025)
This research is motivated by several problems faced by the Bina Usaha Bunda Sharia Cooperative in Gunung Tuleh District, West Pasaman Regency, particularly related to the decline in the number of members and cooperative assets. This study aims to identify development strategies for the Bina Usaha Bunda Sharia Cooperative. The type of research used by the author is field research using qualitative research methods. Data were collected through interviews, direct observation, and documentation. The collected data were analyzed using various methods, including SWOT Analysis, Internal Factor Evaluation (IFE) Matrix Analysis and External Factor Evaluation (EFE) Matrix Analysis, SWOT Matrix, and Score Weighting. The results show that the cooperative has several strengths, such as the implementation of a sharia financial system that attracts the interest of the Muslim community, a low profit margin adjusted to the capabilities of members (1.1%), and fairly transparent management. However, weaknesses include members' low understanding of sharia economics, limited capital and human resources, and weak promotion and digitalization. Opportunities that can be utilized include increasing public awareness of the sharia financial system and the dominance of the trader profession that requires financing. Meanwhile, threats faced are competition between cooperatives and reduced member loyalty. Based on the SWOT analysis, strategies that the cooperative can implement include improving sharia education, optimizing digital promotions, expanding its business network, and building strategic partnerships.